O consumo de substâncias psicoativas por estudantes do ensino superior : $b quais fatores estão associados a essa prática? - Justo, José Maria (2018)
This work problematizes the use of psychoactive substances by students of higher education, whether they are legally permitted or not, whether prescribed or not by health professionals. The main objective of the study is to discuss which internal and extracurricular aspects interfere directly or indirectly in practice. For this, we did a qualitative research, with exploratory character and case study characteristics. For data search, questionnaires were applied with open and closed questions and semi-structured interviews were conducted. The empirical field for the execution of the research was the Ifes campus Cachoeiro de Itapemirim, the public searchedwere the academics enrolled in the face-to-face modality in the courses of Mining Engineering, Mechanical Engineering, Information Systems and math course students. As theoretical study for this question, we turn to the concepts and theses defended by Norbert Elias, so that from these we could propose a critical approach regarding the use of psychoactive substances by students of higher education who hope with this practice to obtain better academic results. At the end of our study, we conclude that the use of psychoactive substances for the purpose of improving school performance is an ordinary practice in the academic field, and that the pressures undergone by students, be they related to the pedagogical and / or evaluative processes present in the daily life of the university, whether they come from the model of society in which we live, based on the premise that personal satisfaction is closely linked to social recognition, and this, it is only possible to realize from the improvement of performance, are the main aspects that interfere in the decision of the university student ofIfes campus Cachoeiro de Itapemirim to resort to the use of psychotropic drugs.